Sosialisasi Pentingnya Cyber Security untuk Menjaga Keamanan Online Studi Fakultas Teknik Informatika Universitas Ibnu Sina - Nofri Yudi Arifin; Okta Veza; Albertus Laurensius Setyabudhi; Atman Lucky Fernandes (Lembaga Pengembangan Kinerja Dosen, 2024)
In the rapidly evolving digital era, cybersecurity has become increasingly crucial as information technology permeates nearly every aspect of life. Students from the Faculty of Informatics Engineering, known for their tendency to adopt new technologies early, face high risks from constantly evolving and complex cyber threats. The importance of cybersecurity cannot be overstated, and educating and socializing safe technology practices are key to protecting oneself from cyberattacks. This community service aims to explore the effectiveness of cybersecurity awareness among students of the Faculty of Informatics Engineering at Ibnu Sina University, focusing on efforts to enhance understanding and protection against online threats. The activities include workshops and involve several stages, from planning to evaluation and reflection. The results indicate a significant improvement in students' understanding and proactive attitudes towards online security practices. Evaluation suggests that these awareness efforts effectively change students' behaviors to enhance digital safety. Recommendations for the future include increasing collaboration between universities and industry to provide additional resources and training. This initiative not only benefits students directly but also serves as a foundation for developing more comprehensive and sustainable cybersecurity education strategies in academic environments.